2019
DOI: 10.1094/phyto-02-19-0040-r
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Soybean Yield and Sudden Death Syndrome Development Using At-Planting Risk Factors

Abstract: In the United States, sudden death syndrome (SDS) of soybean is caused by the fungal pathogen Fusarium virguliforme and is responsible for important yield losses each year. Understanding the risk of SDS development and subsequent yield loss could provide growers with valuable information for management of this challenging disease. Current management strategies for F. virguliforme use partially resistant cultivars, fungicide seed treatments, and extended crop rotations with diverse crops. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Along with these agronomic measures, precision farming practices, such as the quantification of inoculum level and the determination of the disease risk, are being implemented in some countries 45,74,75,89,107‐109 . For example, Roth et al 45 . showed that the quantification of F.v .…”
Section: Cultural Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with these agronomic measures, precision farming practices, such as the quantification of inoculum level and the determination of the disease risk, are being implemented in some countries 45,74,75,89,107‐109 . For example, Roth et al 45 . showed that the quantification of F.v .…”
Section: Cultural Controlmentioning
confidence: 99%
“…Similarly, Roth et al . reported that the additional presence of SCN can increase the risk of severe SDS epidemics 45 . In Argentina, the presence of H. glycines and other nematode species such as Meloidogyne incognita , M. javanica , and Helicotylenchus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The multiple‐pathogen interaction most studied involves F . virguliforme and Heterodera glycines (Brzostowski et al ., 2014; Westphal et al ., 2014; Kandel et al ., 2017; Roth et al ., 2019). H .…”
Section: Fungi–soybean Interactionmentioning
confidence: 99%
“…glycines egg counts. Experimental data were analysed and a risk prediction model for SDS development was implemented (Westphal et al ., 2014; Roth et al ., 2019). Analyses confirmed that the presence of SCN can influence SDS disease severity (Westphal et al ., 2014; Roth et al ., 2019).…”
Section: Fungi–soybean Interactionmentioning
confidence: 99%
See 1 more Smart Citation